Varietal diallel analysis for yield and yield related traits in fennel (Foeniculum vulgare Mill.) - D Singh, Abhay Dashora, R K Sharma, E V D Sastry (Journal of Spices and Aromatic Crops, 2002)
A half diallel of ni ne genetica lly diverse va rieties was made and resulting 36 Fl populations along with the parents were evaluated during rabi 1997-98. The analysis of variance indicated that heterosis was s ignificant for all the characters, except for branches per plant. The heterosis components were also significant for most of the traits studied. Specific heterosis component accounted for more than 50% of the overall heterosis, indicating complex type of inheritance for seed yield and its component traits. The crosses UP (M)-1 x UF-134, RF-125 x JP-29 and UF-90 x HF-7J exhibited significant and positive heterobeltiosis for seed yield per plant.